The effect of age-specific stay-at-home recommendation on healthcare utilization: Evidence from Finland’s COVID-19 policy - Laaksonen, Jukka; Kortelainen, Mika; Salokangas, Henri (Springer Nature, 2026)
Postponements of non-acute care during the COVID-19 pandemic commonly raised concerns about harmful health consequences and increased healthcare costs, particularly among older individuals. Using nationwide register data from Finland, we employ a regression discontinuity design to examine the effect of an age-specific stay-at-home recommendation on healthcare utilization during the first wave of the pandemic. We find that the recommendation reduced non-acute visits, such as dental care, physiotherapy, and specialized care visits, but had no effect on acute care use, including emergency department visits or inpatient stays. The reductions in dental care use were partly compensated for after the lockdown was lifted, but not in other non-acute services. Additionally, we find indicative evidence of a slight increase in mortality during the three-months post-period after the lockdown. Our findings suggest that a Scandinavian-type social distancing recommendation targeting the elderly may reduce non-acute healthcare use in the short term, thereby temporarily alleviating pressure on healthcare resources during a pandemic. However, the absence of rebound in some non-acute services highlight potential unmet needs, which may imply longer-term risks of functional decline, preventable hospitalizations, and associated healthcare costs. These findings point to the importance of policies that ensure continued access to essential non-acute care for older populations.